2012
DOI: 10.1002/eej.21277
|View full text |Cite
|
Sign up to set email alerts
|

Development of frequency stabilizing scheme for integrating wind power generation into an isolated grid

Abstract: Integration of wind power generation into small islands has been one of the demonstration projects in Okinawa Prefecture. Since such integration could degrade power quality including frequency in an island grid, a frequency stabilizing system using flywheels has been installed into a small island. In order to establish a proper frequency stabilizing scheme for the small island, an accurate model of a diesel generator including governor is vital. Therefore, the model was developed based on the measured values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For the constraint on the flow rate ratio, the pressure is found by solving Eq. (14). For the constraint when equality holds for the upper bound on the frequency, Eq.…”
Section: Experimental Methods and Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the constraint on the flow rate ratio, the pressure is found by solving Eq. (14). For the constraint when equality holds for the upper bound on the frequency, Eq.…”
Section: Experimental Methods and Analysis Methodsmentioning
confidence: 99%
“…We modeled [11,12] the power consumption and formalized the conductivity of purified water, then performed sinusoidal response trials and analyses. In other research, cooperative control using a flywheel in an island system has been proposed [14]. In other research, cooperative control using a flywheel in an island system has been proposed [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also has more charge-discharge cycle life than chemical batteries. There are application examples where FESSs are installed as a solution to short-cycle fluctuations because of its long charge-discharge cycle life, and experimental results showed that FESS is effective for this [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, if a generator is connected as is to the electric power system, the problem of frequency fluctuations or voltage fluctuations may occur. A variety of analyses [1][2][3] have been performed to suppress system frequency deviations and combine energy storage systems and hydrogen production equipment in a power system in order to address the problem of frequency deviation. However, these analyses have primarily used real-time simulations, and as a result, substantial amounts of time are required to perform them.…”
Section: Introductionmentioning
confidence: 99%